Efek Inokulasi Trypanosoma Evansi Terhadap Histopatologi Jaringan Syaraf Mencit (Mus Musculus) - Epry Setiawan (VITEK : Bidang Kedokteran Hewan, 2016)
The alms of this was analized research aims to analyze the damage of nerve tissue in the brain of mice (Mus Musculus) inoculated with Trypanosoma evansi. The animal used in this research was 27 male mice. The plan used in this research was the random complete plan (RAL) with one control group and two experimental groups used nine repetitions. Control group (PO) was given aquades, P1 group was inoculated with Trypanosoma evensi 0,2x104 ml by intraperitoneal, and then P2 group was inoculated with Trypanosma evansi 0,2x104 ml by subcutan. In the fourth day after inoculated the mice were sacrificed and taken the brain organ to make histopathology blood smear. The lesi result was analyzed by using scoring Kennedy method, it showed the result, there was a change of histopathology of nerve tissue in the brain organ of mice (Mus Musculus), it was lesion meningitis 33% was in the control group, 100% was in the experimental group 1 (P1), 100% was in the experimental group 2 (P2). Perivascullar cuffing was 0% in the control group, 100% was in the experimental group 1, and 88% was in the experimental group 2. The gained data was processed by using Statistical Program For Science (SPSS) with Krusskall-Wallis Test method and then with Mann-Whitney Test method. The result showed the real differences (P≤0,01) between control group and experimental group 2.